1996
DOI: 10.1103/physrevlett.77.1254
|View full text |Cite
|
Sign up to set email alerts
|

Tachyonlike Excitations in Inverted Two-Level Media

Abstract: Electromagnetic fields dressed by inverted two-level atoms become tachyonlike excitations with group velocities which are faster than c, infinite, or negative. Such excitations describe the stable modes of the medium when it is weakly probed off resonance. The launching of these tachyonlike excitations is discussed, along with a proposed experiment to observe them. Their existence does not violate Einstein causality. [S0031-9007(96)00891-5]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 18 publications
2
50
0
2
Order By: Relevance
“…Furthermore, many theoretical and few experimental work have implied that it is possible to obtain these abnormal velocities without the attenuation observed here [11], [13], [44]- [46], [48]. Therefore, it is natural to ask whether or not these abnormal behaviors are consistent with the requirements of special relativity, which demands no information can be transmitted faster than the speed of light in vacuum.…”
Section: Front and Information In Passive Mediamentioning
confidence: 98%
“…Furthermore, many theoretical and few experimental work have implied that it is possible to obtain these abnormal velocities without the attenuation observed here [11], [13], [44]- [46], [48]. Therefore, it is natural to ask whether or not these abnormal behaviors are consistent with the requirements of special relativity, which demands no information can be transmitted faster than the speed of light in vacuum.…”
Section: Front and Information In Passive Mediamentioning
confidence: 98%
“…On the (very interesting!) experimental side, see the intriguing papers [110]. Let us add here that, via quantum interference effects, it is possible to obtain dielectrics with refraction indices very rapidly varying as a function of frequency, also in three-level atomic systems, with almost complete absence of light absorption (i.e., with quantum induced transparency) [112].…”
Section: Appendix: a Glance At The Experi-mental State-of-the-artmentioning
confidence: 99%
“…Chiao et al [1], [2], [3] have shown that certain "superluminal" effects are possible without violation of standard notions of Einstein causality, i.e., without conveying information faster than the velocity c of light in vacuum. Such effects have been demonstrated experimentally in optical tunneling [4], [5], [6] and in an electric circuit [7].…”
Section: Introductionmentioning
confidence: 99%
“…Questions have been raised about the validity of the latter prediction at the one-photon level, which would correspond to what CKK call an "optical tachyon" [1]. Aharonov, Reznik, and Stern (ARS) [8] have presented general arguments, based on the unitary evolution of the state vector, that "strongly questions the possibility that these systems may have tachyonlike quasiparticle excitations made up of a small number of photons."…”
Section: Introductionmentioning
confidence: 99%